Marginal seal of composite resin restorations photo activated by L.E.D. and halogen-based light - Pineda Mejía, Martha Elena (2012)
Objective: to compare in vitro the marginal seal degree of composite resin restorations photopolomerized with L.E.D light and conventional halogen light, was the objective of this research.It was used 20 healthy molars recently extracted, in each of them, standardized dimensions class V cavities were prepared in the buccal and palatal aspects. Both cavities were filled with nanoparticles composite resin, Filteck Z350 and Single Bond adhesive (3M). Vestibular restaurations were light cured using L.E.D light, and palatal with conventional halogen light. Once restored, the molars were maintained for 48 hours at 37 °C and 100 % humidity. Samples were subjected to 1 % blue methylene solution thermocycling regimen, and then the marginal leakage degree was assessed, making a palatal-vestibule coronal cut, and the evaluation with a stereoscopic microscopy. The frequency of specimens that leakage the colorant, was 85 % for fillings photoactivated with conventional light, and 50 % for L.E.D, this difference was statistically significant (p < 0.05). The most severe degree of colorant penetration in the tooth-restoration interface was evident in 60 % of samples photoactivated with halogen light, and 15 % with L.E.D, the difference was statistically significant (p = 0.004). Under the conditions of this study, it was concluded that marginal seal degree of composite resin fillings was significantly greater with L.E.D light polymerization than conventional halogen light.